2016
DOI: 10.1007/s00210-016-1262-2
|View full text |Cite
|
Sign up to set email alerts
|

Hydroethanolic extract of Baccharis trimera promotes gastroprotection and healing of acute and chronic gastric ulcers induced by ethanol and acetic acid

Abstract: Ethanol is a psychoactive substance highly consumed around the world whose health problems include gastric lesions. Baccharis trimera is used in folk medicine for the treatment of gastrointestinal disorders. However, few studies have evaluated its biological and toxic effects. To validate the popular use of B. trimera and elucidate its possible antiulcerogenic and cytotoxic mechanisms, a hydroethanolic extract of B. trimera (HEBT) was evaluated in models of gastric lesions. Rats and mice were used to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 57 publications
0
15
0
3
Order By: Relevance
“…Moreover, the lyophilized extract of B. trimera showed a reduction of 90% of the lesion area at a dose of 400 mg/kg [29]. On the other hand, the cytoprotective effect of the hydroethanolic extract of this species was evaluated in two models of gastric lesions: induced by ethanol and acetic acid; which showed a significant reduction in the area of the lesion and oxidative stress induced by the consumption of necrotizing agents [30].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the lyophilized extract of B. trimera showed a reduction of 90% of the lesion area at a dose of 400 mg/kg [29]. On the other hand, the cytoprotective effect of the hydroethanolic extract of this species was evaluated in two models of gastric lesions: induced by ethanol and acetic acid; which showed a significant reduction in the area of the lesion and oxidative stress induced by the consumption of necrotizing agents [30].…”
Section: Resultsmentioning
confidence: 99%
“…The anti-secretory and antiulcer activity of B. trimera aqueous extract (1000–2000 mg/kg) was already reported in stress-induced ulcer model and pylorus ligature model [ 34 ] and even in a model of hydrochloric-induced acute gastric ulcers, where a lower dose (100–400 mg/kg) displayed antiulcer activity too [ 35 ]. In a more recent research performed, using a lower dose and a more concentrated B. trimera extract (90%), it was shown that the oral administration of 30 mg/kg significantly reduced the lesion area and the macroscopic appearance of acute and chronic ulcer models [ 36 ]. Also, in a study performed using high doses (1000–2000 mg/kg), the authors proposed that B. trimera inhibits gastric acid secretion by acting on the cholinergic regulatory pathway.…”
Section: Plant Products and Phytochemicals As Antiulcerogenic And mentioning
confidence: 99%
“…Also, in a study performed using high doses (1000–2000 mg/kg), the authors proposed that B. trimera inhibits gastric acid secretion by acting on the cholinergic regulatory pathway. However, Lívero et al [ 36 ] proposed that the effects of B. trimera extract in preventing or reversing ethanol- and acetic acid-induced ulcers may be attributable to the inhibition of free radical generation and subsequent prevention of lipid peroxidation and that flavonoids and caffeoylquinic acids detected in the studied extract play an important and contributive role on these effects.…”
Section: Plant Products and Phytochemicals As Antiulcerogenic And mentioning
confidence: 99%
“…Alcoholism, besides smoking, stress, and H. pylori infection, is considered a risk factor for peptic ulcers. The chronic consumption of ethanol leads to gastric ulceration, reducing mucus production, cell proliferation, and gastric blood flow and promoting an inflammatory response [12]. Figure 1 shows the protective effect of chrysin in the model of gastric ulcer induced by absolute ethanol.…”
Section: Resultsmentioning
confidence: 99%